The Application of Differentiated Learning to Accommodate Differences in Student Learning Styles and Speeds - Saona Saona (Jurnal Pendidikan Indonesia, 2024)
Differentiated instruction is an important approach in responding to differences in learning styles and speeds among students in heterogeneous classrooms. Uniform teaching practices often lead to disparities in engagement and learning outcomes. This study aims to: (1) identify the forms of differentiation strategies used by teachers, (2) analyze the impact of differentiation on student learning engagement, (3) measure changes in learning outcomes between ability groups, and (4) describe students' perceptions of differentiated learning. The research used a qualitative approach with a case study design in the eighth grade of SMPIT Ibnu Khaldun with 40 students. Data were collected through observation, semi-structured interviews, and document analysis, then analyzed with an interactive model through data reduction, presentation, and verification. The results showed that: (1) differentiation strategies were implemented through variations in content, process, product, and learning time; (2) student engagement increased, especially in the low and medium ability groups; (3) there was an increase in learning outcomes in all groups, with the largest increase in the low group; (4) students had positive perceptions because the learning was considered more appropriate to their needs and increased their self-confidence. It was concluded that differentiated learning effectively accommodates differences in learning styles and speeds and strengthens student engagement and achievement.